DOP039 Exploring stoma rates in Crohn's disease in the biologic era: a population-based time trend analysis. (16th January 2018) - Ma, C; Kotze, P G; Almutairdi, A; Tanyngoh, D; Seow, C; Novak, K; Lu, C; Panaccione, R; Kaplan, G
Abstract: Background: Surgical rates for Crohn's disease (CD) in the biologic era are controversial, with discrepancies between population-based studies and referral cohorts. With advances in medical therapy, temporal trends in rates of surgical ostomy creation need to be re-evaluated. Methods: Population-based surveillance was conducted between April 1, 2002 and March 31, 2009 using the Discharge Abstract Database of the Calgary Health Zone. We identified adult patients (≥18 years) admitted for CD who underwent surgical stoma creation ( n = 427). Annual stoma creation incidence for CD was calculated by dividing the number of incident stoma creations by the estimated prevalence of CD within the Calgary Health Zone for each fiscal year. Time trend analysis was performed on the stoma creation rate and the annual percent change (APC) with 95% confidence intervals (CI) was calculated. The APC was calculated using a generalised linear model assuming a Poisson distribution. The analysis was then stratified by emergency vs. elective surgical indication. Statistical analysis was performed using Joinpoint Regression Program (Version 4.5.0.1, National Cancer Institute). Results: The overall stoma creation rate was 1.9 stomas per 100 person-years (PY) (95% CI: 1.5, 2.5). The rate of stoma creation between 2002 and 2009 trended downwards by an average of 5.8% per year (95% CI: −11.4%, 0.2%), from a rate of 2.3 stomas per 100-PY (95% CI: 1.8, 3.0) in 2002 to 1.6 stomas per 100-PY (95% CI: 1.3, 2.1) in 2009. When stratified by surgical indication, the rate of emergency ostomy creations decreased significantly from 2002 to 2009 with an APC of −14.6% (95% CI: −22.8%, −5.6%). In contrast, elective ostomy creation rates remained stable with an APC of 3.1% (95% CI: −2.8%, 9.4%). A shift in the frequency of emergency compared with elective stoma surgery was observed in 2005–2006. At the beginning of the study period, emergency stoma creation rates exceeded elective stoma creation rates (1.3 emergency stomas per 100-PY vs. 1.0 elective stomas per 100-PY), but by the end of the study period, this pattern had reversed (0.6 emergency stomas per 100-PY vs. 1.1 elective stomas per 100-PY). This is illustrated in Figure 1. Conclusions: In this large population-based time trend analysis, we demonstrate a significant reduction in the rates of emergency stoma surgeries for CD with a paradigm shift in surgical care trending towards increasingly elective stoma creation during the biologic era.